The Other Side of the Coin: Nocebo Effects and Psychotherapy - Locher, Cosima; Koechlin, Helen; Gaab, Jens; Gerger, Heike (Frontiers in Psychiatry, 2019)
Psychotherapy as well as placebo have a long history and both have been shown to have significant and clinically meaningful effects. In the last 100 years and up to today, psychotherapy has been subject to an enduring and often heated debate about its mechanisms and its possible relationship to placebos and their effects. However, there is little awareness of the placebo effects’ counterpart – nocebo effects (from Latin “I will harm”) – in the context of psychotherapy. Embedded in the controversy of whether psychotherapy and placebo share some unwanted proximity in terms of effects and mechanisms, the question arises which role nocebo effects may play in relation to psychotherapy. By using two examples, this article analyzes and discusses two different kinds of possible associations between psychotherapy and nocebo effects. We close with possibilities of how to prevent the occurrence of nocebo effects in psychotherapy, including some specific recommendations for clinical practice.